POTENTIAL AREA ESTIMATION OF FISHING GROUND BASED ON THERMAL FRONT AND UPWELLING IN WEST SUMATERA WATERS IN EAST SEASON - Vikri, Ahmad; Siregar, Sofyan H.; Mubarak, Mubarak (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
This research was conducted in August to November 2019. It aims to determine the potential fishing ground based on thermal front and upwelling in the waters of West Sumatra. The survey method was applied in this research. The results showed that the distribution of thermal front and upwelling in the waters of West Sumatra experienced a change that was not too significant. Based on the results of sea surface temperature verification on the Aqua MODIS image with the temperature in the field obtained temperature differences of around ± 10C. The catch during the research shows that catches in the thermal front area can be used as a potential fishing ground because the catch in the thermal front area is more than the area outside the thermal front.